Separation of the Proximal Humeral Epiphysis in the Newborn: Rapid Diagnosis with Ultrasonography - Rachelle Goldfisher; John Amodio (Case Reports in Pediatrics)
Separation of the proximal humeral epiphysis (SPHE) is a well-known occurrence and may occur secondary to trauma, infection, and nonaccidental trauma. Since most newborns do not have the proximal humeral epiphysis ossified at birth, the diagnosis may be difficult to make on routine radiographs. Ultrasonography of the shoulder in the newborn is rapid, noninvasive, and nonionizing imaging techniques which can diagnose SPHE. In this report, we describe and emphasize the diagnostic utility of state-of-the-art ultrasonography for the diagnosis of SPHE.